2011
DOI: 10.4269/ajtmh.2011.11-0001
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses and Avidity of Naturally Acquired Anti-Plasmodium vivax Duffy Binding Protein (PvDBP) Antibodies in Individuals from an Area with Unstable Malaria Transmission

Abstract: Plasmodium vivax remains an important cause of morbidity outside Africa, and no effective vaccine is available against this parasite. The P. vivax Duffy binding protein (PvDBP) is essential during merozoite invasion into erythrocytes, and it is a target for protective immunity against malaria. This investigation was designed to evaluate naturally acquired antibodies to two variant forms of PvDBP-II antigen (DBP-I and -VI) in malaria individuals (N = 85; median = 22 years) who were living in hypoendemic areas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…However, the frequency of the natural antibody responses remained relatively low when compared to those against other classical P. vivax vaccine candidates, such as MSP-1 19 , MSP-9, MSP-3 and AMA-1, which have frequencies that ranged between 60% and 90% of reactivity against their most immunogenic regions [12], [15], [42]. On the other hand, the data is still comparable to proteins such as DBP [43] and the N-terminal region of MSP-9 [44].…”
Section: Discussionmentioning
confidence: 89%
“…However, the frequency of the natural antibody responses remained relatively low when compared to those against other classical P. vivax vaccine candidates, such as MSP-1 19 , MSP-9, MSP-3 and AMA-1, which have frequencies that ranged between 60% and 90% of reactivity against their most immunogenic regions [12], [15], [42]. On the other hand, the data is still comparable to proteins such as DBP [43] and the N-terminal region of MSP-9 [44].…”
Section: Discussionmentioning
confidence: 89%
“…The avidity index (AI) was calculated as the ratio of the OD value of urea-treated samples to that of the untreated samples, multiplied by 100. All AI values less than 30% were considered low-avidity antibodies, values between 30% and 50% were considered intermediate-avidity antibodies, and values greater than 50% were considered high-avidity antibodies (37).…”
Section: Methodsmentioning
confidence: 99%
“…The ELISA results showed that 42.1% of the patients were positive responder for rDBP-IX which was higher than a former study in Iran (32%) [27], however this result was comparable with those from unstable malaria transmission regions such as Colombia (40%) [28] and Brazilian Amazon region (50%) [19]. According to previous studies, the dominance of cytophilicIgG1 and IgG3 subclasses has been reported in response to malaria infection [27,29].…”
Section: Discussionmentioning
confidence: 42%
“…According to previous studies, the dominance of cytophilicIgG1 and IgG3 subclasses has been reported in response to malaria infection [27,29]. The suggested mechanism by which these subclasses are protective includes their binding to the Fc receptors on the monocytes, leading to antibody dependent cell mediated inhibition of the parasite replication.…”
Section: Discussionmentioning
confidence: 97%